Increasing fruit and vegetables consumption among children: a systematic review of animated nutrition interventions - Ifeoluwa Omolara Bodunde, RDN; Alice Karanja, PhD; Stepha McMullin, PhD; Kai Mausch, PhD; Amy Ickowitz, PhD (World Nutrition, 2022)
Background: Low consumption of fruits and vegetables among children can lead to deprivation of micronutrients necessary for growth and development and predispose them to NCDs later in life. Low consumption of these nutrient-rich foods is related to high consumption of nutrient-poor, high-energy foods, which leads to childhood overweight and obesity. Many children do not consume enough fruits and vegetables to meet recommendations. This review aims to assess the effectiveness of animated interventions in increasing children's fruit and vegetable consumption.